2024
DOI: 10.1038/s42003-024-06188-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in somatosensory and cerebellar activity mediate temporal recalibration of self-touch

Konstantina Kilteni,
H. Henrik Ehrsson

Abstract: An organism’s ability to accurately anticipate the sensations caused by its own actions is crucial for a wide range of behavioral, perceptual, and cognitive functions. Notably, the sensorimotor expectations produced when touching one’s own body attenuate such sensations, making them feel weaker and less ticklish and rendering them easily distinguishable from potentially harmful touches of external origin. How the brain learns and keeps these action-related sensory expectations updated is unclear. Here we emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 135 publications
2
1
0
Order By: Relevance
“…This interpretation is consistent with previous findings that physically separating the finger applying a force from the finger receiving it reduces the level of attenuation [5], and that forces that are predictable based on active finger movement but not associated with a contact event do not show attenuation [3,6,17]. The previous evidence that the predictive mechanism can adapt to changes in the causal relationship [35,36] suggests that attenuation might develop in these contexts with sufficient exposure, though this may take considerably longer than a typical experimental session.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This interpretation is consistent with previous findings that physically separating the finger applying a force from the finger receiving it reduces the level of attenuation [5], and that forces that are predictable based on active finger movement but not associated with a contact event do not show attenuation [3,6,17]. The previous evidence that the predictive mechanism can adapt to changes in the causal relationship [35,36] suggests that attenuation might develop in these contexts with sufficient exposure, though this may take considerably longer than a typical experimental session.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with studies that found attenuation and gating are governed by separate mechanisms [13,34], and a range of previous observations supporting a predictive basis for attenuation of self-generated touch, including that attenuation is observed when fingers are expected to make contact even if they fail to do so ( [4]; recently replicated in [6]), whereas attenuation is not observed when the same movement is made without an expectation of contact, or when equivalent forces are presented passively to both fingers [3]. The constant attenuation across different gain conditions implies that the predictive mechanism could update to reflect the new gain relationship, consistent with previous evidence for adaptability of the attenuation process to delays in force transmission [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, these studies either probed perception only at the moment of self-touch (22)(23)(24)(28)(29)(30)(31)(33)(34)(35)(36)(37)(38)(39)57), overlooking the periods before or after the hands' contact, or otherwise focused on the time before the contact (58), overlooking the periods during or after self-touch. Third, other studies have introduced temporal delays to test somatosensory perception before and/or after the predicted self-touch (26,27,32,46,59), but those probed timings were tailored to the moment of the predicted tactile sensation and did not directly relate to the reaching movement of the active hand. For example, one can probe somatosensory perception at a fixed time before the anticipated self-touch, but that timing could align with different phases (early or late) of the active hand's reaching depending on its duration.…”
Section: Introductionmentioning
confidence: 99%